Atrial thrombi in elective patients considered for atrial fibrillation rhythm control: Risk factors and prognostic value - Caires, Marcella Cabral (Indian Heart J, 2021)
The prognostic value of atrial thrombi (AT) among elective patients with atrial fibrillation (AF) referred for a rhythm control strategy is unclear. In this study, clinical variables were correlated with the presence of AT and long term survival among 205 patients submitted to transesophageal echocardiography before elective AF cardioversion or ablation. Atrial thrombi were present in 7.8% of cases and were significantly associated with reduced survival. Obesity was the only independent clinical predictor of AT [OR 4.27 (1.15–15.79), p = 0.03]. In patients with AF, AT appear to be associated with adverse outcomes, possibly indicating more advanced atrial cardiomyopathy.